Metabolomic and transcriptomic responses of Adiantum (Adiantum nelumboides) leaves under drought, half-waterlogging, and rewater conditions - Liang, Qianyan; Dun, Bicheng; Li, Linbao; Ma, Xiaobo; Zhang, Haibo; Su, Yang; Wu, Di (Frontiers in Genetics, 2023)
Adiantum nelumboides (Adiantum) is an endangered fern with a narrow distribution along the Yangtze River in China. Due to its cliff-dwelling habit, it experiences water stress conditions, which further en-dangers its survival. However, no information is available about its molecular responses to drought and half-waterlogging conditions. Here, we applied five and ten days of half-waterlogging stress, five days of drought stress, and rewatering after five days of drought stress, and studied the metabolome profiles and transcriptome signatures of Adiantum leaves. The metabolome profiling detected 864 metabolites. The drought and half waterlogging stress induced up-accumulation of primary and secondary metabo-lites including amino acids and derivatives, nucleotides and derivatives, flavonoids, alkaloids, and phe-nolic acid accumulation in Adiantum leaves. Whereas, rewatering the drought-stressed seedlings re-versed most of these metabolic changes. Transcriptome sequencing confirmed the differential metabolite profiles, where the genes enriched in pathways associated with these metabolites showed similar expres-sion patterns. Overall, the half-waterlogging stress for 10 days induced large-scale metabolic and tran-scriptomic changes as compared to drought stress for 05 days or rewatering for 05 days. This pioneering attempt provides valuable data for a detailed understanding of molecular responses of Adiantum leaves to both drought and half waterlogging stress and rewater conditions. This study also provides useful clues for the genetic improvement of Adiantum for drought/half waterlogging tolerance.